Short-term high-fat diet post-ACLT surgery activates chondrocyte AMPK pathway and slows articular cartilage degeneration in rats - Hongri Ruan; Tingting Zhu; Tianwen Ma; Yun Liu; Jiasan Zheng (Journal of Functional Foods)
Osteoarthritis is often exacerbated by obesity and metabolic syndrome, which are frequently associated with high-fat diets (HFD). This study investigates the direct effects of HFD on articular cartilage following anterior cruciate ligament transection (ACLT) in rats, while also examining the role of free fatty acids (FFA) on chondrocyte activity. Our findings indicate that short-term HFD treatment after ACLT reduces pain sensitivity, alleviates knee swelling, and mitigates cartilage damage. Joint imaging studies, along with serum analyses of inflammatory markers and extracellular matrix (ECM) degradation, further underscore the protective role of post-surgical HFD in maintaining cartilage integrity. Notably, HFD significantly enhances AMP-activated protein kinase (AMPK) phosphorylation in cartilage. In vitro experiments reveal that low concentrations of FFAs stimulate chondrocyte proliferation and energy metabolism, whereas AMPK inhibition leads to elevated expression of inflammatory mediators and ECM-degrading enzymes in chondrocytes. Collectively, these results suggest that short-term HFD following ACLT surgery exerts protective effects on cartilage, primarily through AMPK activation.